Smart specialisation, Industry 4.0 and lagging regions: some directions for policy. Issue 1 (1st January 2020) - Barzotto, Mariachiara; Corradini, Carlo; Fai, Felicia; Labory, Sandrine; Tomlinson, Philip R.
ABSTRACT: At the heart of the European Union's innovation policy is Smart Specialisation Strategy (S3) as embodied in the Research and Innovation Strategies for Smart Specialisation (RIS3) programme. So far, RIS3's efficacy on the revival of so-called lagging regions has been weak. This is in large part due to the weak initial endowments of technology, social/business networks, poor governance and institutional failures that typify lagging regions. This combination inhibits both the effectiveness of the programme and the ability of lagging regions to take advantage of the new opportunities proffered by Industry 4.0. This paper highlights some of these challenges and presents some policy directions for S3 and Industry 4.0 to deliver better regional cohesion and enhance inclusive growth.